Neurodegenerative Disease and the Experience of Homelessness - Piña-Escudero, Stefanie Danielle; López, Lucía; Sriram, Sandeepa; Longoria Ibarrola, Erika Mariana; Miller, Bruce; Lanata, Serggio (Frontiers in Neurology, 2021)
Introduction: Today, half of the American homeless population is older than 50 years of age. This shift in age distribution among people experiencing homelessness has challenged our long-held views of the causes of homelessness. Age-related neurological diseases, especially neurodegenerative diseases of the brain (NDDB), may play a role eliciting homelessness in a significant proportion of vulnerable older adults. This article aims to explore relationships between homelessness and NDDB in a cohort of research participants enrolled in observational studies on NDDB at an academic center. Methods: We reviewed charts of the Memory and Aging Center (MAC) of the University of California, San Francisco's database searching for research participants with NDDB that had direct relationship to homelessness. We reviewed all research visits conducted between 2004 and 2018 (N = 5,300). Research participants who had any relationship to homelessness were included in this analysis. NDDB was diagnosed via comprehensive neurological, functional, neuropsychological, and biomarker assessments. Non-parametric tests were used for analysis. Thirteen participants were found to have a direct relationship with homelessness. Seven were female and the median of education was 16 (IR: 12.0–19.5) years. Participants were divided into two groups: Those who experienced homelessness while symptomatic from a NDDB but before formal diagnosis (n = 5, Group 1); and participants with formally diagnosed NDDB who exhibited a new propensity toward homelessness (n = 8, Group 2). Compared to Group 2, participants in Group 1 were younger (p = 0.021) and showed similar results in the neuropsychological evaluation. In both groups, the most prevalent diagnosis was frontotemporal dementia. In Group 1, the majority of participants became homeless in the setting of a fragile socioeconomic situation and informants believed that NDDB contributed or caused their homeless state. In Group 2, a new propensity toward homelessness became manifest in different ways and it stood out that all of these participants were well-supported by family and friends during their illness. Conclusions and Relevance: This case series highlights the role that NDDB may have in precipitating homelessness among vulnerable older adults, particularly in the setting of challenging socioeconomic circumstances and unsupportive living environments. Social ramifications of these findings, particularly pertaining to challenges around rehousing these individuals is discussed.